Clinical significance of miR-9-5p in NSCLC and its relationship with smoking - Zhang, Tian-Xiang; Duan, Xin-Chun; Cui, Yong; Zhang, Ye; Gu, Meng; Wang, Zi-Yu; Li, Wei-Ying (Frontiers in Oncology, 2024)
Purpose Dysregulated expression of microRNA (miRNAs) in lung cancer has been wildly reported. The clinicopathologic significance of miR-9-5p in non-small-cell lung cancer (NSCLC) patients and its effect on NSCLC progression were explored in this study. Patients and methods A total of 76 NSCLC patients were included. miR-9-5p expression was evaluated by real-time quantitative polymerase chain reaction (RT-qPCR). Then, in vitro experiments including cell growth curve assays, colony formation assays, and transwell migration assays were performed. Further clinicopathological and prognostic values were explored using bioinformatics analysis of the TCGA database. Results miR-9-5p expression was significantly increased in tumor tissues (both P < 0.0001). miR-9-5p expression was relatively higher in larger tumors (P = 0.0327) and in lung squamous carcinoma (LUSC) (P = 0. 0143). In addition, miR-9-5p was significantly upregulated in the normal lung tissues of cigarette smokers (P = 0.0099). In vitro, miR-9-5p was correlated with cell proliferation and migration. After that, bioinformatics analysis of the TCGA database indicated that miR-9-5p was correlated with tumor size (P = 0.0022), lymphatic metastasis (P = 0.0141), LUSC (P < 0.0001), and smoking history (P < 0.0001). Finally, a prognostic study indicated high miR-9-5p expression was correlated with poor prognosis in LUAD (P = 0.0121). Conclusion Upregulation of miR-9-5p may have an oncogenic effect in NSCLC and may be related to smoking. The conclusion of this study may help find new prognostic and therapeutic targets for NSCLC and the exploration of the relationship between smoking and lung cancer.